Morphometric Study of the Lumbar Spinal Canal in the Normal Libyan Population using Computed Tomography - Osama Ambarak; Eiman Aleias; Rehab Benarous; Heithum Baiu; Abdullah Alsherif; Said Almnfe; Ahmed Alsherif; Mohamed Alsherif (AlQalam Journal of Medical and Applied Sciences, 2025)
Precise measurements of the lumbar vertebrae are crucial for spinal surgery and for the placement of medical devices. When the stenosis in the vertebral canal or intervertebral foramen exists, it can press on nerves, leading to symptoms like low back pain or radicular pain (pain radiating down the leg). This study aimed to measure the mid-sagittal diameter and interpedicular distance of the lumbar spinal canal by analyzing computed tomography (CT) scans. This study on 113 Libyan patients (84 males, 29 females) with an age range between 18 to 60 years of age utilized computed tomography (CT) scans to determine the normal values of the midsagittal diameter and interpedicular distance in the normal Libyan population. The study sample included 113 patients, with 74.33% being male (84) and 25.67% female (29). The range of midsagittal diameter at all levels was (10.2-29.1mm). The narrowest level was L3. It is found that L5, the lowest lumbar vertebra, had the largest midsagittal diameter among all the lumbar vertebrae measured, averaging 17.61 mm (with a range of 11.1 to 29.1 mm). The range of interpedicular distance at all levels was (15.6-42.4 mm). The measurement of the lumbar vertebrae showed a steady increase in the interpedicular distance from L1 to L5. Only a small percentage of patients, specifically 3.1%, were found to have a statistically significant midsagittal diameter. The findings of this research could have important clinical implications for surgeons and medical professionals. CT scans provide crucial data, which, when combined with accurate measurements, form the basis for anatomical studies.